PENGARUH BOLA STANDAR DAN BOLA MODIFIKASI TERHADAP KEMAMPUAN PASSING ATAS DALAM PERMAINAN BOLAVOLI PADA MURID SD INPRES TANGKALA II MAKASSAR - Ali Muhaimin (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
This  study  aims  to  determine;  (1)  To  determine  the  extent  of  the  effect  of standard ball size number 4 on the ability of passing on to the elementary  school students Inpres Tangkala II Makassar. (2) To determine the extent of the effect of modifications to the ball passing ability on the elementary school students Inpres Tangkala II Makassar.  (3) To find out which is better effect between standard ball ball size number 4 with modifications to the ability of passing on to the elementary  school students Tangkala II Makassar.Jenis  this study is the kind of experimental  research. The population is all elementary school students Inpres Tangkala II with a sample of 30 people. Further divided into two groups with ordinal matching  technique  is  to  group  standard  15  ball  and  15  ball  modification.   Sampling technique  is technique  saturated  samples. Data analysis technique  used is the paired t-test and  unpaired  t-test.  Based  on  the  results  of  this  study  concluded  that  (1)  a  significant difference using a standard ball against passing ability on elementary school students Inpres Tangkala  II Makassar  City thitung 12.854 and ttabel obtained  a value of 2.045 (0.000 <α0.05);  (2)  a  significant  difference  using  a  modification   to  the  ball  passing  ability  on elementary  school  students  Inpres  Tangkala  II of Makassar  tcount  = 27 798 and table =2,045 while the significant value gained 0,000 <α 0.05. Due to significant levels of less than0.05 α (3) the use of a modified ball better improve significantly the passing on of the use of standard ball at the elementary school students Inpres Tangkala II Makassar City t = 3,358 and the value table = 2,045, while the value of significant obtained 0.002 <α 0:05, because the significance value smaller than α 0:05.